Talking about the institutional complexity of the integrated rehabilitation system – the importance of coordination - Sari Miettinen; Ulla Ashorn; Juhani Lehto (International Journal of Integrated Care, 2013)
Rehabilitation in Finland is a good example of functions divided among several welfare sectors, such as health services and social services.  The rehabilitation system in Finland is a complex one and there have been many efforts to create a coordinated entity. The purpose of this study is to open up a complex welfare system at the upper policy level and to understand the meaning of coordination at the level of service delivery. We shed light in particular on the national rehabilitation policy in Finland and how the policy has tried to overcome the negative effects of institutional complexity. In this study we used qualitative content analysis and frame analysis. As a result we identified four different welfare state frames with distinct features of policy problems, policy alternatives and institutional failure. The rehabilitation policy in Finland seems to be divided into different components which may cause problems at the level of service delivery and thus in the integration of services. Bringing these components together could at policy level enable a shared view of the rights of different population groups, effective management of integration at the level of service delivery and also an opportunity for change throughout the rehabilitation system.